Characterization of Brazilian Cascade and Chinook hops and their dry-hopped beer - GUIMARÃES, Bernardo Pontes; DUTRA, Romulo Coriolano; CARMO, Talita Souza; SUAREZ, Paulo Anselmo Ziani; GHESTI, Grace Ferreira (Food Science and Technology, 2024)
The flowers (cones) of Hop (Humulus lupulus L.) have extensive applications in the brewery industry and in Brazil, 98% of which is imported. The Brazilian cultivated hops have multiple flowerings, and therefore the cone cultivation period could be shortened. Herein, Cascade and Chinook whole cones cultivated in Brazil were analyzed and compared with American pellets. Following the European Brewery Convention (EBC) methodology, the contents of alpha acids, polyphenols, and essential oils were quantified and used as comparison criteria. Amidst the Brazilian Cascade essential oils, isoamyl propanoate and 6-methyl heptanoate were identified, both of which were responsible for pineapple aromas and were absent in American pellets. The dry hopping (DH) process promoted higher alcohol beverage value, lower dissolved oxygen, and higher polyphenol values. In comparison with the commercial counterpart, the Brazilian Cascade hops presented similar characteristics, but with different organoleptic properties (terroir), inherent to their growing place. The resulting terroir adds value to the Brazilian Cascade usage, considering the DH overall process and the application in special beers.